The Effect of Service Quality and Emotional Factors on Users’ Satisfaction: The Case PT Gojek Indonesia in Palembang City - Marisa, Cyntya; Rahayu, Sri; Nurrahmi, maftuhah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to determine 1) the effect of Service Quality (reliability, responsiveness, assurance, empathy, physical evidence) and Emotional Factors on User Satisfaction with the Gojek application at PT. Gojek Indonesia in Palembang City; 2) the effect of Service Quality (reliability, responsiveness, assurance, empathy, physical evidence) on User Satisfaction with the Gojek application at PT. Gojek Indonesia in Palembang City; 3) the effect of Emotional Factors on User Satisfaction of the Gojek application at PT. Gojek Indonesia in Palembang City. This is a causal (verificative) study. The variables used in this study are service quality, emotional factors, and satisfaction. The sample consists of 349 Gojek application users in Palembang City aged 17 years and above, selected through purposive sampling. The primary data used in this study was collected through questionnaires. The data analysis techniques used are Principal Component Analysis (PCA) and Multiple Linear Regression with SPSS software. The results of this study indicate that (1) service quality (reliability, responsiveness, assurance, empathy, physical evidence) and emotional factors have a positive and significant effect on satisfaction; (2) service quality (reliability, responsiveness, assurance, empathy, physical evidence) has a positive and significant effect on satisfaction; (3) emotional factors have a positive and significant effect on satisfaction. The coefficient of determination value indicates that service quality and emotional factors can explain 71.2% of satisfaction, while other variables explain the remaining 28.8%.